2014
DOI: 10.1007/s11356-014-3686-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH, inorganic anions, and dissolved organic matter on the photolysis of antimicrobial triclocarban in aqueous systems under simulated sunlight irradiation

Abstract: The photolysis of the antimicrobial triclocarban (TCC) in aqueous systems under simulated sunlight irradiation was studied. The effects of several abiotic parameters, including solution pH, initial TCC concentration, presence of natural organic matter, and most common inorganic anions in surface waters, were investigated. The results show that the photolysis of TCC followed pseudo-first-order kinetics. The TCC photolysis rate constant increased with increasing solution pH and decreasing the initial TCC concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…However, an early report pointed out that the photodegradation of CZ (15.8 mg/L) under UV-A and UV-B appeared to be pH-dependent (pH = 5.0, 7.0 and 9.0) with the k values range of 0.0099-0.0165 min −1 [22]. Similarily, this contrast may also explain by the difference of photodegradation conditions [19,31,33].…”
Section: Effect Of Ph On the Photodegradation Of Czmentioning
confidence: 96%
See 3 more Smart Citations
“…However, an early report pointed out that the photodegradation of CZ (15.8 mg/L) under UV-A and UV-B appeared to be pH-dependent (pH = 5.0, 7.0 and 9.0) with the k values range of 0.0099-0.0165 min −1 [22]. Similarily, this contrast may also explain by the difference of photodegradation conditions [19,31,33].…”
Section: Effect Of Ph On the Photodegradation Of Czmentioning
confidence: 96%
“…A nearest literature reported that the half-life (t 1/2 ) of CZ under UV-254 was 3.95 min [23], slightly lower than present study (9.78 min), which might cause by the different photodegradation conditions, such as light source (), photo-reactor, initial concentration etc. [19,31,33]. When compared to photodegradation, the chlorine oxidation of CZ was very poor (Fig.…”
Section: Uv Photodegradation Compared To Chlorinationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also a potential carcinogen due to the possibility of carbon-nitrogen bond cleavage, which would generate N-hydroxylated metabolites (Halden and Paull, 2004). In addition, TCC yields mono-and dichloro-anilines as attenuation byproducts in the environment, which are hematotoxic, genotoxic, and persistent (Heidler et al, 2006;Ding et al, 2014).…”
Section: Introductionmentioning
confidence: 99%